Modeling of deformation processes of a "soil-foundation-building" system in the presence of karst phenomena - Tsvetkov, Roman Valer'evich; Shardakov, Igor Nikolaevich (Computational Continuum Mechanics, 2010)
The development of karst phenomena in the soil a foundation rests on poses a hazard to the structure of buildings. The paper presents the results of modeling the deformation behavior of a "soil-foundation-building" system affected by karst processes. The obtained data allowed us to select sensors for automated deformation monitoring, to determine the measurement range of recorded parameters and to find the optimal location of sensors within the monitoring area. The proposed mathematical model can be used in the analytical block of the automated monitoring system.